2022
DOI: 10.3390/nano12101759
|View full text |Cite
|
Sign up to set email alerts
|

One-Dimensional P-Doped Graphitic Carbon Nitride Tube: Facile Synthesis, Effect of Doping Concentration, and Enhanced Mechanism for Photocatalytic Hydrogen Evolution

Abstract: P-doped graphitic carbon nitride tubes (P-CNTS) with different P concentrations were successfully fabricated via a pre-hydrothermal in combination with a calcination process under a nitrogen atmosphere. The as-prepared samples exhibited excellent photocatalytic performance with a hydrogen production rate (HPR) of 2749.3 μmol g−1 h−1, which was 17.5 and 6.6 times higher than that of the bulk graphitic carbon nitride (CNB) and graphitic carbon nitride tube (CNT). The structural and textural properties of the P-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…The good photocatalytic activity of CN-H is due to the porous lamellar structure after hydrothermal pretreatment and the increase of SSA, which can provide more active sites for the reaction. [20,21], respectively, so the VB values of CN-C are determined to be 1.68 eV, 0.12 eV higher than those of CN-H. According to the band arrangement of the REDOX potentials relative to water reduction and oxidation in the figure, it is found that both CN-C and CN-H satisfy the thermodynamic conditions for photocatalytic H 2 production.…”
Section: Influence Of Pretreatment On Hydrogen Production Performance...mentioning
confidence: 95%
“…The good photocatalytic activity of CN-H is due to the porous lamellar structure after hydrothermal pretreatment and the increase of SSA, which can provide more active sites for the reaction. [20,21], respectively, so the VB values of CN-C are determined to be 1.68 eV, 0.12 eV higher than those of CN-H. According to the band arrangement of the REDOX potentials relative to water reduction and oxidation in the figure, it is found that both CN-C and CN-H satisfy the thermodynamic conditions for photocatalytic H 2 production.…”
Section: Influence Of Pretreatment On Hydrogen Production Performance...mentioning
confidence: 95%
“…All starting materials, consisting of urea ((NH 2 ) 2 CO), thiourea ((NH 2 ) 2 CS), ammonium molybdate tetrahydrate ((NH 4 ) 2 Mo 7 O 24 •4H 2 O), hydrogen peroxide (H 2 O 2 ), chloroplatinic acid (H 2 PtCl 6 ), triethanolamine (TEOA), and sodium sulfate (Na 2 SO 4 ) with analytical grade were directly used in our work. The preparation of bulk g-C 3 N 4 (u-CNB) was according to our previous studies [22]. The u-CNB photocatalyst was facilely achieved as follows.…”
Section: Preparation Of Bulk G-c 3 Nmentioning
confidence: 99%
“…Table 6 summarizes diverse mono-heteroatoms including phosphorus [ 76 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 ], sulfur [ 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ], boron [ 115 , 116 , 117 , 118 , 119 , 120 , 121 ], oxygen [ 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 ], carbon [ 135 , 136 , 137 , 138 , 139 ], nitrogen [ 140 , 141 , …”
Section: Heteroatom-doped Porous Carbon Nitridementioning
confidence: 99%
“…Thus, engineering the morphology of gCN nanostructures can benefit the separation and movement of photogenerated charge pairs, facilitate mass transfer, and offer more accessible active sites for catalytic reactions [ 6 , 28 , 100 , 101 ]. For instance, Zhu et al proposed a template-free synthesis of mesoporous phosphorus-doped g-C 3 N 4 nanoflowers (P-CN) with in-plane mesopores (3–18 nm) and open-up surface ( Figure 5 d) by co-condensation and thermolysis of a mixture with ME as g-C 3 N 4 precursor and (hydroxyethylidene) diphosphonic acid as phosphonic source [ 76 ].…”
Section: Heteroatom-doped Porous Carbon Nitridementioning
confidence: 99%